试论宇文所安《剑桥中国文学史》的理念与呈现 = Principle and presentation on the Cambridge history of Chinese literature (Volume I) - 李佳 Li, Jia (2016)
通过对宇文所安教授主编的《剑桥中国文学史》（第一卷）的分析，结合其以往著作中有关编纂文学史的观点，并与袁行霈教授主编的《中国文学史》进行比较，探讨宇文教授新编文学史理念。本文认为《剑桥中国文学史》秉承了历史主义的研究方法，注重接受史的逻辑思维，提出了文学史是对以往文学文化的叙述、文学史本身就是文学史的一部分、经典的形成经过一系列复杂的中介过程等重要观点。此外，新编文学史还特别关注物质文化对文学的作用、文学发展的不确定性，并打破以朝代进行文学分期的传统、较好的贯彻了以文学本位书写文学史的观念，从“旁观者”的视角提出了颇多新见。Based on analyzing the Cambridge History of Chinese Literature (Volume I) edited by Prof. Stephen Owen, combined with his previous researches and compared with the History of Chinese Literature edited by Prof. Yuan Xingpei, this paper discussed Prof. Steven’s writing conception on History of Chinese Literature. The paper put forward that the Cambridge History of Chinese Literature followed the Historicism Methodology and paid much attention to Reception History. The new works held that history of literature is a historical narrative of “Literary Culture”, itself was a part of the literary history, and formation of classical works passed through a series of complicated mediate process. In addition, the new works emphasized on tangible culture’s effects on development of literary history and this development’s indeterminacy. The editors of the new works broke through the traditional division of historical periods and commendably carried out standard outlook of literature. From the angle of “stander-by”, there are some wonderful academic ideas in this new works.